Simultaneous determination of tramadol and paracetamol in human plasma using LC-MS/MS and application in bioequivalence study of fixed-dose combination - Loh, Gabriel Onn Kit; Wong, Emily Yii Ling; Goh, Chen Zhu; Tan, Yvonne Tze Fung; Lee, Yi Lin; Pang, Lai Hui; Shahridzo, Siti Halimah; Damenthi, Nair; Hermansyah, Andi; Long, Chiau Ming; Peh, Kok Khiang (Annals of medicine (Helsinki), 2023)
The study aimed to develop a sensitive and high-throughput liquid chromatography coupled with tandem mass spectrometry method to quantify concentrations of tramadol and paracetamol simultaneously in human plasma. Sample preparation involved single-step protein precipitation using methanol and two deuterated internal standards, tramadol D6 and paracetamol D4. Agilent Poroshell 120 EC-C18 (100 × 2.1 mm, 2.1 µm) analytical column was employed to achieve chromatographic separation. Detection was in positive ion multiple reaction monitoring mode. A tailing factor (Tf) of <1.2, separation factor (K prime) of >1.5 from the column dead time and signal-to-noise (S/N) ratio >10, were obtained for analytes and internal standards. The standard curve was linear over the concentration range of 2.5-500.00 ng/mL for tramadol and 0.025-20.00 μg/mL for paracetamol. A small injection volume of 1 µL, low flow rate of 440 µL/min and short analysis time of 3.5 min reduced the solvent consumption, analysis cost and system contamination. The results of method validation parameters fulfilled the acceptance criteria of bioanalytical guidelines. The method was successfully applied to a bioequivalence study of fixed-dose combination products of tramadol and paracetamol in Malaysian healthy subjects.The study aimed to develop a sensitive and high-throughput liquid chromatography coupled with tandem mass spectrometry method to quantify concentrations of tramadol and paracetamol simultaneously in human plasma. Sample preparation involved single-step protein precipitation using methanol and two deuterated internal standards, tramadol D6 and paracetamol D4. Agilent Poroshell 120 EC-C18 (100 × 2.1 mm, 2.1 µm) analytical column was employed to achieve chromatographic separation. Detection was in positive ion multiple reaction monitoring mode. A tailing factor (Tf) of <1.2, separation factor (K prime) of >1.5 from the column dead time and signal-to-noise (S/N) ratio >10, were obtained for analytes and internal standards. The standard curve was linear over the concentration range of 2.5-500.00 ng/mL for tramadol and 0.025-20.00 μg/mL for paracetamol. A small injection volume of 1 µL, low flow rate of 440 µL/min and short analysis time of 3.5 min reduced the solvent consumption, analysis cost and system contamination. The results of method validation parameters fulfilled the acceptance criteria of bioanalytical guidelines. The method was successfully applied to a bioequivalence study of fixed-dose combination products of tramadol and paracetamol in Malaysian healthy subjects.